Design Design the temperature and humidity classification of the workspace by using a decision tree model. - Wahyu Setiady; Y.B. Adyapaka Apatya (LPPM Poltek ST Paul, 2020)
Design the temperature and humidity classification of the workspace by using a decision tree model. Based on the standard table of technical planning procedures for energy conservation in buildings, the optimal comfortable temperature is in the range of 22.8 oC - 25.8 oC with a threshold of 28 oC and humidity of 70%. By utilizing the decision tree classifier, the temperature and humidity of the room detected by the DHT11 sensor are classified based on a model that has been created using Raspberry Pi 3 and the node red. This research was carried out in the ATMI Industrial Polytechnic computer laboratory which is also used as an applied research laboratory in collaboration with industry in the field of automation software development. This research succeeded in making a classification tool for temperature and humidity of the workspace by using a decision tree model that produces a status of cold, cool comfortable, optimal comfort, warm comfort and heat with a predicted level of 0.983.